The signal that stimulates mammalian embryo development - Machaty, Zoltan (Frontiers in Cell and Developmental Biology, 2024)
Embryo development is stimulated by calcium (Ca 2+ ) signals that are generated in the egg cytoplasm by the fertilizing sperm. Eggs are formed via oogenesis. They go through a cell division known as meiosis, during which their diploid chromosome number is halved and new genetic combinations are created by crossing over. During formation the eggs also acquire cellular components that are necessary to produce the Ca 2+ signal and also, to support development of the newly formed embryo. Ionized calcium is a universal second messenger used by cells in a plethora of biological processes and the eggs develop a "toolkit", a set of molecules needed for signaling. Meiosis stops twice and these arrests are controlled by a complex interaction of regulatory proteins. The first meiotic arrest lasts until after puberty, when a luteinizing hormone surge stimulates meiotic resumption. The cell cycle proceeds to stop again in the middle of the second meiotic division, right before ovulation. The union of the female and male gametes takes place in the oviduct. Following gamete fusion, the sperm triggers the release of Ca 2+ from the egg's intracellular stores which in mammals is followed by repetitive Ca 2+ spikes known as Ca 2+ oscillations in the cytosol that last for several hours. Downstream sensor proteins help decoding the signal and stimulate other molecules whose actions are required for proper development including those that help to prevent the fusion of additional sperm cells to the egg and those that assist in the release from the second meiotic arrest, completion of meiosis and entering the first mitotic cell division. Here I review the major steps of egg formation, discuss the signaling toolkit that is essential to generate the Ca 2+ signal and describe the steps of the signal transduction mechanism that activates the egg's developmental program and turns it into an embryo.